Function analysis of GhWRKY53 regulating cotton resistance to verticillium wilt by JA and SA signaling pathways - Li, Youzhong; Chen, Haihong; Wang, Youwu; Zhu, Jincheng; Zhang, Xiaoli; Sun, Jie; Liu, Feng; Zhao, Yiying (Frontiers in Plant Science, 2023)
WRKY transcription factors (TFs) play an important role in regulating the mechanism of plant self-defense. However, the function of most WRKY TFs in upland cotton (Gossypium hirsutum) is still unknown. Hence, studying the molecular mechanism of WRKY TFs in the resistance of cotton to Verticillium dahliae is of great significance to enhance cotton disease resistance and improve its fiber quality. In this study, the type III WRKY transcription factor gene GhWRKY53 in upland cotton was identified and obtained. Different disease-resistant cotton varieties inoculated with V. dahliae showed that GhWRKY53 mediated salicylic acid (SA) and methyl jasmonate (MeJA) signal transduction pathways. After virus-induced gene silencing (VIGS) of the GhWRKY53 gene, the ability of cotton to resist V. dahliae decreased, indicating that the GhWRKY53 gene could be involved in the disease resistance mechanism of cotton. Studies on the levels of SA and jasmonic acid (JA) and their related pathway genes demonstrated that the silencing of GhWRKY53 inhibited the SA pathway and activated the JA pathway, thereby reducing the resistance of plants to V. dahliae. In conclusion, GhWRKY53 could change the tolerance of upland cotton to V. dahliae by regulating the expression of SA and JA pathway-related genes.